Bibliografski projekt društva bibliotekara Federacije Bosne i Hercegovine / Bibliographic Project of the Library Association in Federation of Bosnia and Herzegovina - Hajdarpašić, Lejla (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
This text is a review of the book Bibliography of the Bulletin of Library Association and National library of the People's Republic of Bosnia and Herzegovina and journal Librarianship: 1955-2001. by Nadina Grebović-Lendo, Muamera Smajić, Merima Karamović and Alma Felić, Sarajevo, Library Association in Federation of Bosnia and Herzegovina, 2016, pp. 148.